Judging Competency A study of in-training evaluation of veterinary students : A thesis presented in partial fulfilment of the requirements for the degree of Doctor of Education at Massey University, Manawatū, New Zealand - Norman, Elizabeth J (Massey University, 2016)
In-training evaluations are a common but highly criticised method of assessing the competency of veterinary students completing training. They involve assessment of on-going performance in the workplace, performed by the supervisor. They are highly feasible and one of the few ways that a student’s performance in an authentic context can be evaluated. Psychometric research has suggested, however, that in-training evaluations are unreliable, do not discriminate aspects of performance, and do not predict performance on other assessments, casting doubt on the credibility of scores. Research on rater judgement processes suggests, in contrast, that multiple aspects are discriminated and that accounting for context and inferred reasons for behaviour contributes to rater variability. Very little research has considered in-training evaluation in a veterinary context. In a mixed method study this research investigated how well the in-training evaluation used during clinical placements in one veterinary school captured the aspects of student performance it was designed to capture. It explored the supervisor’s view of student performance, and how that related to the dimensions being assessed in in-training evaluation, and to the constructs of competency articulated in frameworks. Complementary research strands involved analysis of semi-structured interviews with supervisors, common factor analysis of in-training evaluation scores, ordinal logistic regression relating factors to overall judgement, and thematic comparisons of findings with competency frameworks. Together, the nature of what supervisors considered, the dimensional structure of scores, and the relationship of dimensions with the overall judgement suggested that the in-training evaluation is both holistic and discriminating, and that important aspects of performance are student engagement and trustworthiness. The aspects captured by the evaluation aligned well with the design of the instrument, and generally well with the veterinary competency frameworks. However, some areas were highlighted where concepts of veterinary competency and the competencies required in different subdisciplines need further consideration by the profession. The findings give insights into the process of judgement of competency by veterinary supervisors that will inform further research. They support some aspects of a validity argument in relation to scoring processes, and inform the design of evaluation instruments by underscoring the construct-relevance of interrelated dimensions.
Listed in 2016 Dean's List of Exceptional Theses
Keywords: Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education; Dean's List of Exceptional Theses